Apoptosis and Redistribution of the Ro Autoantigen in Balb/c Mouse Like in Subacute Cutaneous Lupus Erythematosus - Rafael Herrera-Esparza; Ricardo Villalobos; Juan-Jose Bollain-y-Goytia; Roxana Ramírez-Sandoval; Sergio H. Sánchez-Rodriguez; Guadalupe Pacheco-Tovar; Esperanza Avalos-Diaz (Clinical and Developmental Immunology)
In subacute cutaneous lupus eryhematosus (SCLE) the cutaneous antigens constitute the main source of Ro and La autoantigens. The aim of this investigation was to demonstrate if UV light increases the availability of Ro autoantigen in the skin, also the blocking effect of Ac-DEVD-CMK a caspase inhibitor was assessed. For this purpose newborn Balb/c mice were UVB irradiated (5–30 mJ/cm2) equivalent to a moderate to severe sunburn. Animals were injected with monoclonal anti-Ro antibodies from SCLE patients. Apoptosis was also induced by anti-Fas antibody injection. Skin samples were examined by direct immunofluoresence, by TUNEL, and the expression of caspase 3 by RT-PCR. Major findings of present studies were: 1. UVB irradiation and anti-Fas induced apoptosis of keratinocytes. 2. Apoptosis redistribute the Ro antigen on cell surface and is better triggered by Ro antibody. 3. The caspase 3 inhibitor Ac-DEVD-CMK decreases the availability of Ro autoantigen in epidermis and prevents deposition of anti-Ro. In conclusion, the caspase pathway would be blocked to avoid anti-Ro deposition along skin; this finding would be a prospect in the treatment of SCLE patients.